Strategic Partitioning of Emissions Allowances. Under the EU Emission Trading Scheme - Christoph Böhringer; Knut Einar Rosendahl (Statistics Norway, Research Department, 2008)
The EU Emission Trading Scheme (ETS) is breaking new ground in the experience with emission trading regimes across multiple jurisdictions. Since the EU ETS covers only some industries, it implies a hybrid emission control scheme where EU member states must apply complementary domestic emissions regulation for the non-trading sectors of their economies in order to comply with their national emission reduction targets. The EU ETS thus opens up for strategic partitioning of national emissions budgets by the member states between trading and non-trading sectors. In this paper we examine the potential effects of such strategic behavior on compliance cost and emissions prices. We show that concerns on efficiency losses from strategic partitioning are misplaced if all the member states behave in a Nash-Cournot manner. However, if a single country takes the official partitioning of the other countries as a reference point, there is substantial scope for exploiting market power.
Keywords: C61; C72; Q25; 330; Emissions Trading; Allocation of Quotas; Strategic Behavior